Contemporary Anti-Gratification Frameworks in State Islamic Religious Colleges: Strategic Pathways for Building a Competitive Civilization - Zulfahmi; Muhamad Hasan Sebyar; Mualimin Mochammad Sahid (Islamic Research Publiser, 2024)
State Islamic Religious Colleges (PTKIN) play a strategic role in building a competitive and ethical civilization through the application of integrity values and the prevention of gratification practices. This contemporary research aims to introduce and explore the dynamics of effective gratification prevention, with a primary focus on innovative and adaptive strategies in PTKIN. Employing a qualitative approach that integrates literature review and case study methods, this study seeks to construct a comprehensive framework for contemporary anti-gratification governance within Islamic higher education. The findings reveal that the innovation of anti-gratification frameworks has been effectively institutionalized across several PTKIN, producing significant impacts on institutional competitiveness, ethical culture, and sustainable academic development. Integrity and transparency within the academic environment serve not only as preventive mechanisms against corruption but also as foundational elements for shaping a generation of morally conscious and globally competitive scholars. The academic contribution of this study lies in its contextual integration of Islamic ethical principles with contemporary governance practices, offering a transformative model for anti-gratification policy implementation in higher education. Furthermore, PTKIN has operationalized anti-gratification initiatives through various strategic actions, including the establishment of dedicated Research Centers, the incorporation of Anticorruption Education into curricula, capacity-building programs, socialization for students and academic staff, and active collaboration with the Corruption Eradication Commission (KPK). These efforts collectively demonstrate PTKIN’s commitment to fostering integrity-based education as a cornerstone of contemporary Islamic civilization.